2016
DOI: 10.1158/0008-5472.can-15-3444
|View full text |Cite
|
Sign up to set email alerts
|

The Widening Sphere of Influence of HOXB7 in Solid Tumors

Abstract: Strong lines of evidence have established a critical role for the homeodomain protein, HOXB7, in cancer. Specifically, molecular and cellular studies have demonstrated that HOXB7 is a master regulatory gene, capable of orchestrating a variety of target molecules, resulting in the activation of several oncogenic pathways. HOXB7 overexpression correlates with clinical progression and poor outcome of cancer patients. Specific inhibition of HOXB7 is particularly relevant in cancers still lacking effective therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…HOXB7 is commonly believed to be dysregulated in several types of cancers and associated with cancer progression [24]. HOXB7 upregulation has been demonstrated in colorectal cancer and esophageal squamous cell carcinoma, and HOXB7 has been shown to indicate poor prognosis in individuals with both these diseases [20, 21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOXB7 is commonly believed to be dysregulated in several types of cancers and associated with cancer progression [24]. HOXB7 upregulation has been demonstrated in colorectal cancer and esophageal squamous cell carcinoma, and HOXB7 has been shown to indicate poor prognosis in individuals with both these diseases [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its expression has been correlated with clinical progression and poor outcome and may serve as a potential prognostic factor and therapeutic target [11, 14, 19, 20, 22, 23]. HOXB7 is involved in many of the major cellular processes that occur in cancer, including proliferation, invasion, migration, angiogenesis and the epithelial–mesenchymal transition (EMT) [24]. Furthermore, HOXB7 has been reported to facilitate the migration of breast [25] and liver [18] cancer cells by inducing EMT, and ectopic expression of HOXB7 promotes angiogenesis [9, 26] and cell proliferation [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally recognized that HOXB7 is dysregulated in several types of cancers and associated with cancer progression [ 10 ]. HOXB7 up-regulation has been demonstrated in gastric cancer and shown to indicate poor prognosis in gastric cancer patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Homeobox B7 (HOXB7), a member of homeobox gene family, has been shown to be involved in several cancers, including gastric [ 6 ], oral [ 7 ], pancreatic [ 8 ] and breast cancer [ 9 ]. As an important transcription factor, HOXB7 regulates many cancer cell functions, including proliferation, invasion, migration, angiogenesis and epithelial-mesenchymal transition (EMT) [ 10 ]. It has been reported that the proliferation and self-renewal of haematopietic stem cells are enhanced by HOXB7 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…One functional study highlighted MAGI2-AS3 as a bladder cancer suppressor (Wang et al, 2018), while the other study focused on its effects on breast cancer cell growth (Yang et al, 2018). A member of HOX family, HOXB7 has also been highlighted to participate in a variety of crucial cellular processes during oncogenesis (Errico et al, 2016), with particular involvement in gastric cancer, wherein its over-expression promoted cell migration and invasion while restraining cell apoptosis (Joo et al, 2016). More importantly, over-expression of HOXB7 imparts reduced sensitivity of oral cancer cells to chemo-radiotherapy (Yuan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%